Systematic Literature Review: Pengaruh Kinerja Keuangan, Corporate Social Responsibility, Koneksi Politik, dan Transparansi Laporan Keuangan terhadap Penghindaran Pajak. - Shobrina Nurul Aisyah; Sinta Apriyani; Vita Khera Amelia; Dien Noviany Rahmatika (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of financial performance, Corporate Social Responsibility (CSR), political connections, and financial report transparency on tax avoidance using the Systematic Literature Review (SLR) approach. Tax avoidance practices remain a significant issue in Indonesia because they can reduce potential state revenue and reflect weak corporate governance. This research method analyzes 45 scientific articles indexed by Sinta in the 2020-2025 period. These articles were selected through a screening stage using the keywords "Tax Avoidance", "Financial Performance", "CSR", "Political Connections", "Financial Report Transparency". The selection process was carried out through academic search engines such as Google Scholar, Semantic Scholar, Sinta, and Connected Paper. The analysis was conducted descriptively to assess the consistency of previous research results and identify research gaps. Hasilll…. Practically, the results of this study are expected to be a reference for regulators and policymakers in tightening the transparency of financial reporting and fiscal supervision to suppress tax avoidance practices in Indonesia.